MESIN PENGERING KERUPUK HEMAT ENERGI UNTUK MENINGKATKAN PRODUKTIVITAS PRODUSEN KERUPUK - Sudiyatno, Sudiyatno; Rachmad, Suprapto (Universitas Negeri Yogyakarta, 2004)
The objective of producing a low energy drying machine is to help chips industries in increasing their productivity by shortening the drying time. Up to now they use heat of sunlight to dry the chips.This process is time consuming and why the dry season comes, the process isdelayed. It decreases the quality of chips.The drying machine produced uses firewood placed in a furnace as the heat source. The heat is then flown through pipes into the drying room, where wet chips are placed. iiThe room has a length of 1.2 m, a height of 1 m and a width of 1 m. It has twodoors and equipped with a thermometer. Below the room, there is a furnace having capacity of 6 kg tire wood and an oxygen inlet. The drying temperature is 60 - 70° C. I kg firewood can produce the heat with temperature of 60 - 70° C for 1.5 hours.The drying process of wet- chips takes about 5 hours. For that of half dry chips, it takes 2hours. This machine has capacity of2.400 wet chips and 6.000 half dry chips.